CRITICAL FACTORS INFLUENCING THE ADOPTION OF TAX DIGITALIZATION: A PATH TO A SUSTAINABLE TAX PROFESSION - Rabaatul Azira Hassan; Maheran Zakaria; Murugan Batumalai; Noor Marini Abdullah; Mohd Hisham Mahamud (International Journal of Accounting, Finance and Business, 2024)
The rapid advancement of digital technology has significantly influenced multiple areas, including taxation. Converting tax-related information into digital format has numerous advantages, including simplifying tax procedures, lessening administrative responsibilities, improving productivity, and strengthening data protection. To date, tax professionals in advanced economies have turned their attention to digitalization to offset the complexity of their work and ensure the profession's sustainability. Nevertheless, Malaysian tax professionals are currently still in the early stages of adopting tax digitalization. Therefore, this conceptual study aims to investigate the factors that would expedite the adoption of digitalization in taxation among tax professionals using the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. By examining performance expectancy, effort expectancy, social influence, and facilitating conditions on tax professionals' acceptance and use of tax digitalization, this study will inform policymakers, professional bodies, and tax authorities formulate plans and strategies to promote the widespread adoption of tax digitalization that will lead to a more efficient and sustainable tax profession. This move aligns with the Malaysian government's aspirations and the United Nations Sustainable Development Goal 9 of promoting inclusive and sustainable growth of the industry through innovation.